Structural organization and biological activity of molecular clones of the integrated genome of a BALB/c mouse sarcoma virus. - Andersen, P R (1981)
BALB/c mouse sarcoma virus (BALB-MSV) is a spontaneously occurring transforming retrovirus of mouse origin. The integrated form of the viral genome was cloned from the DNA of a BALB-MSV-transformed nonproducer NRK cell line in the Charon 9 strain of bacteriophage lambda. In transfection assays, the 19-kilobase-pair (kbp) recombinant DNA clone transformed NIH/3T3 mouse cells with an efficiency of 3 X 10(4) focus-forming units per pmol. Such transformants possessed typical BALB-MSV morphology and released BALB-MSV after helper virus superinfection. A 6.8-kbp DNA segment within the 19-kbp DNA possessed restriction enzyme sites identical to those of the linear BALB-MSV genome. Long terminal repeats of approximately 0.6 kbp were localized at either end of the viral genome by the presence of a repeated constellation of restriction sites and by hybridization of segments containing these sites with nick-translated Moloney murine leukemia virus long terminal repeat DNA. A continuous segment of at least 0.6 and no more than 0.9 kbp of helper virus-unrelated sequences was localized toward the 3' end of the viral genome in relation to viral RNA. A probe composed of these sequences detected six EcoRI-generated DNA bands in normal mouse cell DNA as well as a smaller number of bands in rat and human DNAs. These studies demonstrate that BALB-MSV, like previously characterized avian and mammalian transforming retroviruses, arose by recombination of a type C helper virus with a well-conserved cellular gene.